IOT- Smart irrigation with tracking system using NodeMCU ESP8266 - Shawky, Negm Eldin Mohamed (International Journal of Scientific Research in Computer Science and Engineering, 2023)
This paper reviews the Smart Irrigation with tracking System which is an automated system that uses sensors, sensed data, and algorithms to optimize water usage for irrigation. This system can be controlled remotely through a smartphone or other mobile device, making it easy for farmers and homeowners to monitor and adjust their irrigation systems from anywhere. the involved sensors connected to a microcontroller in the system can be used to measure soil moisture, air temperature, humidity, and also to monitor using camera undesired animals or persons in a specified area for taking a decision against them. The sensed data that can be obtained from the sensors is received by mobile applications using the WebSocket communication protocol, which is analyzed by an algorithm to determine the optimal amount of water required for the plants. It is also used to track daily farm duties, grow crops, and protect them from harmful insects, rodents, mice, and theft. This system can be programmed to turn on and off at specific times or based on certain conditions, such as soil moisture levels or weather patterns. The benefits of this system include reducing water waste, improving crop yield, send alerts or notifications to users in case of any issues or critical situations and minimizing the cost of labor associated with manual irrigation.